The Pursuit of Risk - Dorman, John (My University, 2013)
John Dorman is the Assistant EM Director for Geospatial and Technology Management in the North Carolina Division of Emergency Management. In this capacity, he is responsible for the design, acquisition, analysis, and dissemination of data, models, systems and applications associated with hazard and threats. Mr. Dorman has facilitated and managed the statewide acquisition of LiDAR-derived elevation data, digital orthophotography, building footprints, and special flood hazard areas. Mr. Dorman is currently managing three national risk management demonstrations: Integrated Hazard Risk Management; Digital Flood Risk; and, Sea Level Rise Impact Study.
Keywords: Hurricanes; Emergency management; NCEM; Emergency disaster